Conociendo la ley: la práctica de Nam Myoho Rengue Kyo en la Soka Gakkai argentina = Knowing the law : Nam Myoho Rengue Kyo's practice at the Argentine Soka Gakkai - Welsch, Denise (Ciencias sociales y religión, 2016)
Soka Gakkai is a japanese buddhist organization that claims that the most effective way of manifest the buddhahood is invoking Nam myoho rengue kyo. Believers affirm that thanks to this practise they changed their lives, and refer to it´s efficency in order to attract new members. To understand this, we will analyze Nam myoho rengue kyo in it´s double carácter of practise and concept, considering the definition given by Soka Gakkai Argentina and the way it´s members interpret and experiment it. We will take Marcel Mauss´s analysis of the prayer and the perspective of Paul Ricouer about the symbols, considering their apparent meaning such as the hidden meaning, comprehensible only through the interpretation of the firt one. We will refer to Lévi-Strauss´s “symbolic efficiency” to understand why it is said that this symbol is efficient, trying to understand the practise and beliefs of one of the biggest buddhist organizations in the country.